Mechanics of bipedalism : an exploration of skeletal morphology and force plate analysis - Forse, Erin (Archaeological Studies Program, University of Wisconsin-La Crosse, 2007)
There are several theories on how humans learned to walk, and while these all address the adaptations needed for walking, none adequately describes how our early ancestors developed the mechanism to walk. Our earliest recognizable relatives, the australopithecines, have several variations on a theme: walking upright. There are varied changes as australopithecines approach the genus Homo. These changes occurred in the spine, legs, pelvis, and feet, and changes are also in the cranium, arms and hands, but these are features that may have occurred simultaneously with bipedalism. Several analyses of Australopithecus afarensis, specifically specimen A.L. 288-1 ("Lucy"), have shown that the skeletal changes are intermediate between apes and humans. Force plate analyses are used to determine if the gait pattern of humans resembles that of apes, and if it is a likely development pattern. The results of both these analyses will give insight into how modern humans developed bipedalism.
Keywords: Bipedalism